2021
DOI: 10.1093/bib/bbab236
|View full text |Cite
|
Sign up to set email alerts
|

Consensus clustering of single-cell RNA-seq data by enhancing network affinity

Abstract: Elucidation of cell subpopulations at high resolution is a key and challenging goal of single-cell ribonucleic acid (RNA) sequencing (scRNA-seq) data analysis. Although unsupervised clustering methods have been proposed for de novo identification of cell populations, their performance and robustness suffer from the high variability, low capture efficiency and high dropout rates which are characteristic of scRNA-seq experiments. Here, we present a novel unsupervised method for Single-cell Clustering by Enhancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…First 3530 Snap25+ neurons were clustered by using the SCENA method [ 71 ] and the results were plotted via UMAP [ 67 ] ( Figure 3 a). The numbers of TRAPed FR and NF cells in the five largest clusters are shown in Figure 3 b.…”
Section: Resultsmentioning
confidence: 99%
“…First 3530 Snap25+ neurons were clustered by using the SCENA method [ 71 ] and the results were plotted via UMAP [ 67 ] ( Figure 3 a). The numbers of TRAPed FR and NF cells in the five largest clusters are shown in Figure 3 b.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no quantitative way to choose which parameter setting is "best" and so the community turns to a number of heuristic objectives to quantify the performance of a workflow. For example, Cui et al (7) attempt to optimize the adjusted Rand index (ARI) with respect to expert annotations and a heuristic based around downsampling rare cell types while minimizing runtime. Germain et al (1) similarly consider the ARI but also the average silhouette width to maximize cluster purity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in ensemble clustering ( Ghaemi et al, 2009 ; Vega-Pons and Ruiz-Shulcloper, 2011 ; Boongoen and Iam-On, 2018 ) have demonstrated that integrating various basic cell partitions in a consensus matrix is effective to generate improved clustering solutions ( Kiselev et al, 2017 ; Zhu et al, 2020 ; Cui et al, 2021 ; Wang et al, 2021 ). The rationale for this idea is to construct a cell-to-cell pairwise similarity matrix based on the diverse basic clustering results through a cluster-based similarity partitioning algorithm (CSPA) ( Strehl and Ghosh, 2002 ), with each value in the matrix representing the probability of the occurrence of cell pairs in the same cluster.…”
Section: Introductionmentioning
confidence: 99%